WORK SPECIFICATION OF EFFECT AND REWARD ON EMPLOYEE EFFECTIVENESS - I Made Bagus Dwiarta; Sindy Eka Prasetya; Subakir Subakir; Fachrudy Asj'ari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The company will be able to compete with competitors if it successfully implements the planned strategy, business challenges that continue to occur make the company increasingly experiencing great pressure to be able to maintain its business from current competition, the company must implement a strategy that can be used as a way out to deal with this situation . In addition, the company must continue to maximize its resources in order to contribute to the company, the company can provide training or direction to employees to work effectively and efficiently considering the company's liability burden continues to grow from year to year. The population and samples used in this study were employees of PT. The charm of Arnos Beton numbered 70 people. The results of the tests that have been carried out show that job specifications and rewards affect the work effectiveness of PT. Enchantment of Arnos Concrete either partially or simultaneously.